2018
DOI: 10.1055/s-0036-1591861
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Flow Reductive Alkylation: Synthesis of Bio-based Symmetrical and Disymmetrical Ethers

Abstract: For the first time, a reductive alkylation process in continuous flow has been elaborated for the conversion of bio-based alcohols and aldehydes into symmetrical and dissymmetrical high-value-added ethers for industrial companies. The developed method is an etherification associating liquid, solid and gas phases under green conditions (continuous flow, catalysis, bio-based starting materials).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To better understand the benefits of utilizing high mass yield fermentation intermediates for the production of AOAs, a life cycle analysis (LCA) was completed for a hypothetical large-scale AOA production facility. The modeled process utilizes industrial acid catalysts for both the esterification and etherification steps that have been demonstrated at large scale for related esterification and etherification reactions . For this analysis, an average carbon conversion efficiency of 0.45 g/g for fusel alcohols and 0.97 g/g for lactate was assumed based on the net theoretical yield of the respective biochemical pathways (Figure ).…”
Section: Environmental Assessment Of Aoasmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the benefits of utilizing high mass yield fermentation intermediates for the production of AOAs, a life cycle analysis (LCA) was completed for a hypothetical large-scale AOA production facility. The modeled process utilizes industrial acid catalysts for both the esterification and etherification steps that have been demonstrated at large scale for related esterification and etherification reactions . For this analysis, an average carbon conversion efficiency of 0.45 g/g for fusel alcohols and 0.97 g/g for lactate was assumed based on the net theoretical yield of the respective biochemical pathways (Figure ).…”
Section: Environmental Assessment Of Aoasmentioning
confidence: 99%
“…The modeled process utilizes industrial acid catalysts for both the esterification and etherification steps that have been demonstrated at large scale for related esterification and etherification reactions. 31 For this analysis, an average carbon conversion efficiency of 0.45 g/g for fusel alcohols and 0.97 g/g for lactate was assumed based on the net theoretical yield of the respective biochemical pathways (Figure 4). 1,32 4.1.…”
Section: Environmental Assessment Of Aoasmentioning
confidence: 99%
“…The first studies on ether synthesis via RER were reported by Doyle and co-workers in the early 1970s. Various symmetrical and unsymmetrical ethers were synthesized in good yields in these studies, whereby harsh acidic conditions were required. Following these seminal studies, many improvements have been made by various groups to synthesize ethers via RER under milder conditions while maintaining high product yields. The RER chemistry was first applied at the macromolecular level, thanks to successive studies by Yokozawa and coworkers starting in the mid-1990s. In the group’s first study, isophthalaldehyde was subjected to a self-condensation polymerization reaction in CH 2 Cl 2 using triethylsilane (Et 3 SiH) as the reducing agent and trityl perchlorate as the catalyst.…”
Section: Introductionmentioning
confidence: 99%